Território usado e recursos hídricos: o uso da água na produção de flores e plantas ornamentais em Holambra-SP - Lopes, Alan Peterson [UNESP] (2015)
The city of Holambra, located in São Paulo, is the major producer of flowers and ornamental plants in Brazil. His intense productive specialization can be seen from the technical apparatus installed there, where huge greenhouses and a lot of irrigation equipment draw your landscape. The cultivation of flowers is differentiated from other crops in Brazil, its production takes place on small farms with many workers, but also requires large number of inputs and resources, such as water resources. Therefore, Holambra have many water captation systems at your territory, which has caused setbacks in water availability of their watersheds. In this scenario, the objective proposed for this work is to analyze the importance of using water resources in the production of flowers and ornamental plants in Holambra, trying to identify the social and environmental vulnerabilities generated by the corporate use of this resource, which is indispensable to the life of any individual